A reconfigurable high Q epsilon near zero tunnel for material characterization. Issue 4 (2nd October 2018) - Peñaloza-Delgado, Rosario; Kaur Kataria, Tejinder; Roberto Reyes-Ayona, José; Luis Olvera-Cervantes, José; Corona-Chávez, Alonso
Abstract: A new type of reconfigurable sensing cavity is designed for measurement of complex dielectric permittivity of materials. This circuit is based on an Epsilon Near Zero (ENZ) tunnel integrated on a substrate, and it uses liquid metal switches to reconfigure two tunneling frequencies (2.4 GHz, and 3.5 GHz). As opposed to conventional narrow channel ENZ structures, our tunnel offers high unloaded quality factor by increasing its volume and controlling its external coupling. Using the cavity perturbation technique, the permittivities of 5 different liquids were measured giving very close results to those reported in the literature.